Enhancing and monitoring the anaerobic digestion of wastewater sludge - Csatordai Viktória (Proceedings of the International Symposium on Analytical and Environmental Problems, 2022)
The most important key of wastewater treatment is the treatment of the wastewater sludge. Anaerobic fermentation is an effective solution for the treatment. It can lower the organic content of the sludge while a renewable energy source – biogas – is produced at the same time. Our research is focused on the applicability of rheological and dielectric measurements to study if these measurements can monitor the proccess of anaerobic digestion. Moreover, microwave pre-treatment was used on the wastewater sludge to examine its effect on anaerobic digestion. Our experimental results represent that the microwave irradiation can intensify the total biogas yield by 15% during anaerobic fermentation. Furthermore, microwave irradiation was effect on viscosity, it reduced the viscosity of the fermentation media by 13%. It has been confirmed that dielectric and rheological measurements are capable of monitoring the anaerobic digestion because there is a correlation among dielectric parameters, biogas yield and absolute viscosity of the fermentation media. Changes in the dielectric parameters and absolute viscosity show similar trends, which can be explained by the connection with biogas production.